(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Over the past few years, patient satisfaction surveys have been used to provide an indication of patient experience. However, patient satisfaction surveys do not accurately describe the feelings and experiences that are actually felt by patients. Using patient experience measurements can provide information on what events occur when getting services at health facilities, measure aspects that are important to patients and see their point of view that can improve the quality of health services. Objective: The study aimed at analyzing the best strategy to be implemented to improve the quality of service for Provincial General Hospital at South Sulawesi based on patient experience. Methods: The study design was quantitative with descriptive analysis approach. A sample of 382 patients was determined and selected with the certain criteria. Data were collected using a measuring instruments in the form of a patient experience questionnaire which contains 48 questions. Results: In these three hospitals, admission to hospital and hospital ward environment are two dimensions of the patient experience that have had unsatisfactory outcomes. Meanwhile, at the Sayang Rakyat Hospital, they have unsatisfactory care and treatment dimensions. Conclusions: This study highlights the relevance of utilizing IPA to evaluate patient perspectives of hospital services and suggest opportunities for improvement. Hospitals can improve patient experience and overall service quality by concentrating on the most critical dimensions in which the hospital is performing poorly (Quadrant A). The study's findings can help hospital stakeholder to identify the methods in order to improve patient experience and satisfaction.